Kepemimpinan dan Inovasi Sektor Publik: Kunci Sukses Otonomi Daerah - Jurnal Governance Jurnal Kebijakan & Manajemen Publik; Falih Suaedi (Governance, JKMP (Governance, Jurnal Kebijakan & Manajemen Publik), 2010)
Some successes stories of local government in the autonomy era, has proven urged by the courage of leader to make and apply innovations strategies. Keep in mind here is that not all changes are innovations, when the changes made an impact even less favorable for society and government. The role of leader is to determine the existence of innovation and organiza-tional change processes. But innovations and changes will not be run effectively when not supported by the parties affected by these changes both internal and external. In facts, there are many local governments that are still managed under the old pattern, that more advanced the power orientation and less put forward the spirit of public services orientation. Public managers who are committed and really want to realize these commitments are the souls that entrepreneurs seize opportunities as well as weaknesses smartly and follow them with prob-lem solving actions-oriented and increasing outputs. These leaders seem to become really agent of change and transformative leader.